Analysis of Transpulmonary Thermodilution Data Confirms the Influence of Renal Replacement Therapy on Thermodilution Hemodynamic Measurements. (May 2016) - Schmidt, Sven; Westhoff, Timm; Schlattmann, Peter; Zidek, Walter; Compton, Friederike
Abstract : BACKGROUND: Transpulmonary thermodilution (TPTD) is used frequently in the intensive care unit to determine cardiac index (CI), intrathoracic blood volume index (ITBVI), and extravascular lung volume index (EVLWI). Renal replacement therapy (RRT) influences TPTD results, but the underlying mechanisms are not completely understood. We hypothesized that RRT blood flow induces errors in TPTD measurements. METHODS: We analyzed TPTD data available from the PiCCO® plus hemodynamic measurement device on a personal computer using a proprietary Pulsion Medical Systems software. By using the dialysis catheter to inject the thermal indicator, 20 measurement series were performed in 12 intensive care unit patients determining CI, ITBVI, and EVLWI during RRT with the blood pump stopped, and at flows of 100 and 200 mL/min, respectively. RESULTS: Data export was successful in 17 measurement series and showed a significant decrease in measured CI (6.5 ± 2.5 vs 5.4 ± 1.9 L/min/m 2, P < 0.001) and ITBVI (1358.8 ± 274.5 vs 1132.8 ± 218.3 mL/m 2, P < 0.001) with RRT and a significant increase in EVLWI (8.6 ± 4.4, 10.2 ± 4.5 mL/kg, P < 0.001). Blood temperature before and the temperature decrease after injection of the thermal indicator were unchanged by RRT. Mean transit time and downslope time of the thermodilution curve, however, were both increased with the RRT blood pump running ( P ⩽ 0.001). CONCLUSIONS: Analysis of TPTD data shows that thermodilution curve forms are modified with RRT, resulting in an erroneous calculation of thermodilution-derived hemodynamic parameters. Abstract : Published ahead of print February 26, 2016